High-performance and flexible solid-state supercapacitors based on high toughness and thermoplastic poly(vinyl alcohol)/NaCl/glycerol supramolecular gel polymer electrolyte. (20th November 2019) - Peng, Shuijiao; Jiang, Xingzong; Xiang, Xiaotong; Chen, Kai; Chen, Guoqi; Jiang, Xiancai; Hou, Linxi
Abstract: In this work, the high-performance and flexible solid-state supercapacitors were fabricated based on poly(vinyl alcohol)(PVA)/NaCl/glycerol hydrogel electrolyte and activated carbon electrodes. A novel assembling method was proposed according to the formation properties of PVA/NaCl/glycerol hydrogel electrolyte. PVA/NaCl/glycerol hydrogel electrolyte could be quickly formed in a short time at room temperature. Thus the PVA/NaCl/glycerol solution was coated onto the activated carbon electrodes and the hydrogel electrolyte was in situ formed on the surface of the activated electrodes. Meanwhile, the PVA/NaCl/glycerol hydrogel electrolyte could retain outstanding flexibility and ionic conductivity at a low temperature, which makes the solid-state supercapacitor have excellent low-temperature tolerance. Thus, the electrochemical measurements of the assembled supercapacitor were performed at room temperature and a low temperature of −23 °C, respectively. The flexible supercapacitor can show an outstanding flexibility and electrochemical performance at −23 °C. Its specific capacitance can remain approximately 81.0% of its initial specific capacitance at room temperature and the capacitance retention could keep 90.5% of the initial capacitance retention at −23 °C. It also could be anticipated that this multifunctional flexible supercapacitor with the PVA/NaCl/glycerol hydrogel electrolyte would have broad applications in modern flexible energy storage device.